Auto-avaliação e avaliação do parceiro: estratégias para o desenvolvimento da metacognição e o aperfeiçoamento do processo de ensino-aprendizagem - Murad, Raissa Rodrigues (2005)
The main objective of this research was to verify if the self-assessment and/or partner s assessment are efficient keys to the construction and development of the metacognition, known as a very important aspect for the improvement of the learning and teaching process. The research was held in a very well known school in the city of São Luís in the state of Maranhão. 24 sixth graders and their mathematics teacher were the participants of the research. The students were supposed to evaluate themselves as they developed some tasks at a specific period of time, and also evaluate their partners. These partners could either be same sex or opposite sex. The data collection also involved the students opinions as to how it was doing this kind of activity, and the teachers inferences about the development of the project. To the results analysis five different categories of the use of metacognition were built, as the students were put in a situation in which they had to do a self-assessment or partner s assessment they tend to use the metacognition, and they improve it as long as they are practicing it. Then it becomes possible to notice which are the positive and the negative aspects about themselves and their partners, promoting in most of cases a real improvement of their own learning process.